The influence of the urban environment on the human mental health - Samofalov, D. V.; Shliapina, Olesia; Шляпіна, Олеся Володимирівна; Шляпина, Олеся Владимировна (My University, 2019)
In order to preserve our psychological health, we can borrow the positive experience of others, and at least not repeat their mistake.
Keywords: the environmental factors; exposure to motor traffic sound; reduction of noise